Catalyzing transformative futures in food and farming for global sustainability - Bhagwat, Shonil A. (Frontiers in Sustainable Food Systems, 2022)
This perspective article highlights the need for transformation in food and farming at three scales to promote a food system that meets UN Sustainable Development Goals. Food insecurity is still a persistent problem globally because of how food and farming sector is currently organized vs. how it should be organized if cultural traditions, environmental concerns, and nutritional needs of the world’s growing population were foregrounded. The article argues that system-wide transformations are needed at different scales: landscape (macro), species (meso) and genes (micro). It suggests alternatives available for food and farming sector and identifies transformative pathways that are more sustainable in cultural, social and environmental terms. A better management of farming landscapes; diversification of the food system to include a wider range of species; and better use of neglected and underutilized species, varieties and cultivars of plants, and breeds of animals in the food system can help to catalyze such a transformation. This can go a long way in promoting global sustainability by achieving three key UN Sustainable Development Goals 2 (Zero Hunger), 3 (Good Health and Wellbeing) and 15 (Life on Land).